Polyglutamine domain flexibility mediates the proximity between flanking sequences in huntingtin - Caron, Nicholas Stephane (National Academy of Sciences, 2013)
Huntington disease (HD) is a neurodegenerative disorder caused by a CAG expansion within the huntingtin gene that encodes a polymorphic glutamine tract at the amino terminus of the huntingtin protein. HD is one of nine polyglutamine expansion diseases. The clinical threshold of polyglutamine expansion for HD is near 37 repeats, but the mechanism of this pathogenic length is poorly understood. Using Förster resonance energy transfer, we describe an intramolecular proximity between the N17 domain and the downstream polyproline region that flanks the polyglutamine tract of huntingtin. Our data support the hypothesis that the polyglutamine tract can act as a flexible domain, allowing the flanking domains to come into close spatial proximity. This flexibility is impaired with expanded polyglutamine tracts, and we can detect changes in huntingtin conformation at the pathogenic threshold for HD. Altering the structure of N17, either via phosphomimicry or with small molecules, also affects the proximity between the flanking domains. The structural capacity of N17 to fold back toward distal regions within huntingtin requires an interacting protein, protein kinase C and casein kinase 2 substrate in neurons 1 (PACSIN1). This protein has the ability to bind both N17 and the polyproline region, stabilizing the interaction between these two domains. We also developed an antibody-based FRET assay that can detect conformational changes within endogenous huntingtin in wild-type versus HD fibroblasts. Therefore, we hypothesize that wild-type length polyglutamine tracts within huntingtin can form a flexible domain that is essential for proper functional intramolecular proximity, conformations, and dynamics.